Pattern of Admission of Common Medical Diseases During the Year 2015 to Sulaimani Teaching Hospital - Hassan, Khalid Ali (Diyala Journal of Medicine, 2019)
Background:The main reasons for admission to the medical wards in high –income countries are non communicable diseases While communicable diseases are the main reasons for admission to the medical wards in low and middle income countries. However, the reasons for admission are changing from communicable diseases to non-communicable diseases in some low and middle income countries. Objective: To assess the frequency and the pattern of medical diseases for patients admitted to the medical wards of Sulaimani Teaching Hospital during the year 2015. Patients and Methods: A retrospective study was conducted in Sulaimani Teaching Hospital for 26700 medical records of the patients who were admitted to the medical wards during the year 2015 (started from 1st January to 31th December), All the patients that had been admitted to the medical wards of Sulaimani Teaching Hospital during the year 2015 were referred from medical emergency department and outpatient clinics in addition to the private clinics. The data were obtained from medical records of the patients in statistic unit of the hospital. The variables involved in the study included age of the patients, gender, residency and final diagnosis. Results: This study included 26700 patients that have been admitted to Sulaimani Teaching Hospital, 14853 (55.62%) were females and 11847(44.38%) were males. Most admitted age groups were between 51- 60 years (18.16%) followed by 61-70 years (17.52%) ,71 years and more (16.58%) , 41-50 years (14.92%) ,21-30 years (13.36%) , 31-40 years (12.79%) while the least admitted age group was less than 20 years (6.67%), 62.85% of the patients were from urban areas and 37.15% were from rural areas. Gastroenteritis was the most common medical illness (6.45%), followed by CerebroVascular Accidant CVA (6.27%),Chronic Obstructive Pulmonary Disease COPD (5.52%),Hypertension HT (4.25%),Diabetes Mellitus DM (4.23%),Bronchial Asthma (2.80%),Heart Failure HF (2.60%),Pneumonia (2.28%),Urinary Tract Infection UTI(1,92%),Anaemia (1.86%) ,Miscellaneous diseases(35.78%) and finally the diseases that not diagnosed (26.04%).The highest number of admissions were in Summer comprising (26.96%) of all admissions followed by in Autumn (25,10%) then in Spring (24,34%) and the lowest in Winter comprising (23.60%) of all admissions.The highest number of admission were in July comprising (9.42%) of all admissions followed by June(8.87%), October(8.72%),August(8.68%),May(8.43%),September(8.36%) December(8.30%),April(8.15%),November(8.02%),January(7.97%),March(7.76%) and the lowest in February(7.32%) of all admissions. Conclusion: The commonest age group for admission is 51-60 year. Admission rate more common in females than in males and it is more common in Summer than in Winter. There is a seasonal variation in the hospital admission. The non-communicable diseases represent the main causes for medical admission than the communicable diseases.